Short-Term Results of Switch from Conbercept to Bevacizumab or Ranibizumab in Eyes with Persistent Neovascular Age-Related Macular Degeneration - Zongyi Wang; Mengyang Li; Yuou Yao; Jie Hu; Jiyang Tang; Ran Tang; Zhenyu Piao; Jinfeng Qu (Journal of Ophthalmology)
Purpose. To study the short-term anatomical and functional outcomes in patients with neovascular age-related macular degeneration (nAMD) who were previously treated with conbercept and switched to ranibizumab or bevacizumab due to persistent activity. Methods. This retrospective single-arm study included nAMD patients who were followed up for at least three months after switching from at least 3 monthly intravitreal conbercept injections to bevacizumab or ranibizumab for persistent choroidal neovascularization (CNV) activity. The demographic data, treatments, best-corrected visual acuity (BCVA), central macular thickness (CMT), and the height of pigmented epithelial detachment (PED) before and after switching were recorded and analyzed. Results. A total of 64 eyes of 64 patients were included with a mean follow-up of 9.6 ± 3.0 months. The average number of injections of conbercept was 3.6 ± 0.8 (range, 3–5) before switching. 18 eyes were switched to bevacizumab, and the other 46 eyes were switched to ranibizumab. After switching, mean BCVA slowly improved from 0.73 ± 0.48 to 0.64 ± 0.41 (p=0.0132) at one month after the last intravitreal injection of ranibizumab or bevacizumab during the mean follow-up of 4.4 ± 2.0 months. One month after switching, the mean CMT decreased significantly from 294.9 ± 121.8 μm to 230.9 ± 107.0 μm (p<0.0001) and kept stable during the follow-up. There was a significant reduction of maximum PED height (mPEDH) at the first month after switching (from 384.3 ± 340.3 μm to 287.2 ± 245.2 μm, p=0.0018) and kept stable during the follow-up. The mean PED height at foveal center (cPEDH) showed a regression over time after switching (from 169.3 ± 230.6 μm to 130.5 ± 180.2 μm, p=0.0227) and also kept stable during the follow-up. The proportion of patients with IRF was slightly increased but not statistically significant before switching. After switching, this proportion decreased significantly from 96.9% to 81.3% at one month after the first intravitreal injection of ranibizumab or bevacizumab (p=0.0086). The proportion of patients with SRF did not change significantly before and after switching. The mean decrease of mPEDH and cPEDH at the last follow-up after switching was significantly larger in the IVR subgroup than in the IVB subgroup (p=0.023 and 0.010). Conclusion. Our results indicate that switching from intravitreal conbercept injections to bevacizumab or ranibizumab can lead to significant improvement of CMT, PED, and IRF and slight improvement of BCVA in a short period of time for persistent nAMD patients.